2014
DOI: 10.1111/bjh.12811
|View full text |Cite
|
Sign up to set email alerts
|

CpG island methylator phenotype of myelodysplastic syndrome identified through genome‐wide profiling of DNA methylation and gene expression

Abstract: SummaryThe CpG island methylator phenotype (CIMP) is an epigenetic phenomenon and plays an important role in tumourigenesis in various cancers. The identification of aberrant DNA methylation can be exploited for early diagnosis and risk assessment of patients. We identified a CIMP in myelodysplastic syndrome (MDS). Genes were screened for hypermethylation and transcription downregulation through genome-wide DNA methylation profiling and gene expression microarrays. Methylation-specific, real-time, and bisulfit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Nonetheless, the differentially methylated genes specific in the combination treatment underline the important contribution of demethylation to the synergistic effect. This profile might serve as the basis for the identification of a methylation signature that is predictive of clinical response as shown in myelodysplastic syndrome (49) or to a limited extent suggested recently in CTCL (50).…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, the differentially methylated genes specific in the combination treatment underline the important contribution of demethylation to the synergistic effect. This profile might serve as the basis for the identification of a methylation signature that is predictive of clinical response as shown in myelodysplastic syndrome (49) or to a limited extent suggested recently in CTCL (50).…”
Section: Discussionmentioning
confidence: 94%
“…Both of these findings suggest a link between iron and leukemogenesis. Concerning the mechanism, DNA methylation is considered to be associated with the pathogenesis and exacerbation of MDS [23][24][25][26][27]. In this study, we first demonstrated that iron overload activated the ACO1-IDH pathway in the TCA cycle and led to increased 2-HG activity, which induced DNA methylation, a critical epigenetic aberration process.…”
Section: Discussionmentioning
confidence: 68%
“…α-KG acts as a substrate of the TCA cycle, whereas it is utilized in many other reactions including DNA demethylation [20,21]. Recently, IDH mutation and the up-regulation of DNA methylation were also predicted to be independent prognosis factors in patients with MDS [22][23][24][25][26][27]. Therefore, the mechanism of aberrant DNA methylation in patients with MDS is to be elucidated further.…”
Section: Introductionmentioning
confidence: 99%
“…The CIMP-high phenotype has been associated with an adverse prognosis in clear cell carcinoma of the kidney (Arai et al 2012), melanoma (Tanemura et al 2009), and myelodysplastic syndrome (Zhao et al 2014). By contrast, a methylation analysis of a large set of breast cancer cohort recently demonstrated a lower risk for metastatic failure in the CIMPpositive group (Fang et al 2011).…”
Section: The Cpg Island Methylator Phenotype In Cancermentioning
confidence: 99%